1991
DOI: 10.1002/1097-0142(19910401)67:7<1865::aid-cncr2820670709>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease in association with human immunodeficiency virus infection. Pathologic and immunologic features

Abstract: Six patients with Hodgkin's disease (HD) and demonstrable serum antibodies to human immunodeficiency virus (HIV) and two additional patients with HD belonging to HIV-associated high-risk groups but with negative HIV serology were studied. All patients were men and ranged in age from 21 to 45 years. The HIV risk factors included homosexuality (6), intravenous drug abuse (2), and hemophilia A (1). All patients had high pathologically determined stage (one Stage III and seven Stage IV), and bone marrow involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 43 publications
(1 reference statement)
1
8
1
Order By: Relevance
“…We confirmed previous findings of a severely altered microenvironment in HIV-associated Hodgkin lymphoma with decreased CD4 numbers in the tissue. [6][7][8][9] Although previous studies observed an inverted CD4/CD8 T-cell ratio, we showed that this is merely due to decreased CD4 numbers, whereas the absolute number of CD8 þ T-cells was stable in HIV-positive and HIV-negative cases. Interestingly, this study showed significantly increased numbers of CD163 þ macrophages in HIV-related Hodgkin lymphoma, whereas the numbers of S100 þ dendritic cells and Hodgkin-and Reed-Sternberg cells were similar between HIV-positive and HIV-negative cases.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We confirmed previous findings of a severely altered microenvironment in HIV-associated Hodgkin lymphoma with decreased CD4 numbers in the tissue. [6][7][8][9] Although previous studies observed an inverted CD4/CD8 T-cell ratio, we showed that this is merely due to decreased CD4 numbers, whereas the absolute number of CD8 þ T-cells was stable in HIV-positive and HIV-negative cases. Interestingly, this study showed significantly increased numbers of CD163 þ macrophages in HIV-related Hodgkin lymphoma, whereas the numbers of S100 þ dendritic cells and Hodgkin-and Reed-Sternberg cells were similar between HIV-positive and HIV-negative cases.…”
Section: Discussioncontrasting
confidence: 67%
“…5 As HIV infection usually involves decreased CD4 þ T-cell counts in the peripheral blood, several studies have addressed the issue of the microenvironment in HIV-associated Hodgkin lymphoma and have found the CD4/CD8 T-cell ratio to be inverted. [6][7][8][9] However, the number of cases examined was very small in the majority of the studies 6,8,9 (o10 HIV-positive classical Hodgkin lymphoma cases each). Thompson et al 7 analyzed 47 HIV-positive Hodgkin lymphoma cases and found a 'sarcomatoid' pattern of the reactive microenvironment to be significantly associated with an adverse clinical outcome.…”
mentioning
confidence: 99%
“…Following these inclusion criteria, 19 articles [1,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] on HD and AIDS published in the English literature between 1988 and 1998 were the subject of our review. Seventeen articles [1,10,11,12,13,14,15,16,17,18,20,22,23,24,25,26,27], for a total of 532 patients, reported data on the histological distribution of HD in the setting of HIV infection, according to the Rye modifications of the classification of Lukes and Butler.…”
Section: Selection Of the Papersmentioning
confidence: 93%
“…Seventeen articles [1,10,11,12,13,14,15,16,17,18,20,22,23,24,25,26,27], for a total of 532 patients, reported data on the histological distribution of HD in the setting of HIV infection, according to the Rye modifications of the classification of Lukes and Butler. We assumed that the Lukes and Butler classification was a valid instrument to provide as much uniformity as possible to retrospective histological data from the literature.…”
Section: Selection Of the Papersmentioning
confidence: 98%
“…In addition, single cases from small series showing features potentially similar to IBM-HIV-HL as defined in the present study have been reported (17,18), although selection criteria were not clearly specified. All cases hereby reported were diagnosed on the basis of detection of classical ReedSternberg cells with typical immunophenotype in the bone marrow; furthermore, strict selection criteria for isolated bone marrow involvement were adopted, and the single patient (Case 2) who, despite the lack of clinically evident lymphadenopathy, underwent a lymph node biopsy failed to show nodal HL.…”
Section: Discussionmentioning
confidence: 99%